FARMER-LED RESEARCH IN THE QUEST FOR CLIMATE RESILIENCE: PROMISING DREAMS BITTER CHALLENGES - Abazaami, J.; Anab, C.; Santuah, N. F. (UDS International Journal of Development, 2022)
Increasing accumulation of ecological, economic and societal challenges characterise Ghana’s agricultural systems, raising questions about the resilience of smallholders (who dominate the sector) to shocks and stresses. The question of resilience brings into sharp focus the aerial differentiations and spatial associations observed in the regional contexts within which climate resilience is sought. The conversation around issues of climate resilience has tended to view smallholders as end users of research results as opposed to co-creators of knowledge pertinent to the subject matter. In Ghana, very little literature, if any, exists about farmers leading the process of knowledge generation to improve our understanding of climate resilience, particularly, in light of how smallholders understand it in the context of their farming systems, farmer organizations, services and value chain actions. This paper highlights the unconventional route of farmer-researchers working with and through their colleagues to unravel the contextual realities of climate resilience and to cast the findings thereof to conventional sources to identify points of convergencies, divergences and the nuances therefrom to lay bare the question of “whose reality counts?” in the resilience conundrum. The methodology consisted of a mixed-methods approach explicated through a convergent parallel design. The findings are that, farmers’ sensitivity to climate change is high and their adaptive capacity is low, necessitating more support for effective resilience building, not from the lenses of ivory tower theorization models of mainstream science, but in a better appreciation of farmers’ articulation of the science of what it takes to build their resilience. Keywords: Farmer-led research, Vulnerability, Resilience, Transformability, Robustness, Adaptability